Fungicides have transgenerational effects on Rhopalosiphum padi but not their endosymbionts. Issue 11 (4th August 2022) - Chirgwin, Evatt; Yang, Qiong; Umina, Paul A; Gill, Alex; Soleimannejad, Safi; Gu, Xinyue; Ross, Perran; Hoffmann, Ary A
Abstract: BACKGROUND: While several agricultural fungicides are known to directly affect invertebrate pests, including aphids, the mechanisms involved are often unknown. One hypothesis is that fungicides with antibacterial activity suppress bacterial endosymbionts present in aphids which are important for aphid survival. Endosymbiont‐related effects are expected to be transgenerational, given that these bacteria are maternally inherited. Here, we test for these associations using three fungicides (chlorothalonil, pyraclostrobin and trifloxystrobin) against the bird cherry‐oat aphid, Rhopalosiphum padi, using a microinjected strain that carried both the primary endosymbiont Buchnera and the secondary endosymbiont Rickettsiella . RESULTS: We show that the fungicide chlorothalonil did not cause an immediate effect on aphid survival, whereas both strobilurin fungicides (pyraclostrobin and trifloxystrobin) decreased survival after 48 h exposure. However, chlorothalonil substantially reduced the lifespan and fecundity of the F1 generation. Trifloxystrobin also reduced the lifespan and fecundity of F1 offspring, however, pyraclostrobin did not affect these traits. None of the fungicides consistently altered the density of Buchnera or Rickettsiella in whole aphids. CONCLUSIONS: Our results suggest fungicides have sublethal impacts on R. padi that are not fully realized until the generation after exposure, and these sublethal impacts are not associated with the density of endosymbionts harbored by R. padi . However, we cannot rule out other effects of fungicides on endosymbionts that might influence fitness, like changes in their tissue distribution. We discuss these results within the context of fungicidal effects on aphid suppression across generations and point to potential field applications. © 2022 Society of Chemical Industry. Abstract : Fungicides (chlorothalonil, pyraclostrobin and trifloxystrobin) have transgenerational effects on Rhopalosiphum padi but not their endosymbionts ( Buchnera Rickettsiella ).